1998
DOI: 10.1046/j.1471-4159.1998.70020786.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid‐Metabolizing Enzymes in Alzheimer's Disease: Increased Lysophospholipid Acyltransferase Activity and Decreased Phospholipase A2 Activity

Abstract: Damage to brain membrane phospholipids may play an important role in the pathogenesis of Alzheimer's disease (AD); however, the critical metabolic processes responsible for the generation and repair of membrane phospholipids affected by the disease are unknown. We measured the activity of key phospholipid catabolic and anabolic enzymes in morphologically affected and spared areas of autopsied brain of patients with AD and in matched control subjects. The activity of the major catabolic enzyme phospholipase A2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
2
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 34 publications
9
71
2
7
Order By: Relevance
“…Although consistent with the upregulation in cPLA 2 and LPCAT activities observed in AD and in response to A␤ 42 (3,4,9), the specificity of this metabolic disruption was nonetheless surprising . Disruption in the Land's cycle predicts a general increase in PAF metabolism not the hydrolysis of structural lipids with specific carbon chain lengths (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Although consistent with the upregulation in cPLA 2 and LPCAT activities observed in AD and in response to A␤ 42 (3,4,9), the specificity of this metabolic disruption was nonetheless surprising . Disruption in the Land's cycle predicts a general increase in PAF metabolism not the hydrolysis of structural lipids with specific carbon chain lengths (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…These metabolites are biologically active in their own right and can be further modified by lysophosphatidylcholine acyltransferases (LPCATs). LPCAT activity also increases in AD (9), notably in the posterior-temporal entorhinal cortex, a region characterized by the earliest tau pathology (2). Transfer of a long-chain acyl group to the sn-2 position by LPCAT1 and LPCAT2 regenerates structural membrane lipids, whereas addition of a small acetyl group produces a family of powerful lipid second messengers known as platelet activating factors (PAFs) (10,11).…”
mentioning
confidence: 99%
“…The hydrolysis of membrane phosphatidylcholine releases free choline that is a substrate for the synthesis of acetylcholine, an important neurotransmitter that has been implicated in the pathophysiology of AD. Changes in PLA2 activity have been demonstrated in various neuropsychiatric disorders such as temporal lobe epilepsy [60] , schizophrenia [61][62][63][64] , and AD [65,66] . Experimental models have shown that PLA2 influences APP processing and secretion.…”
Section: Platelet Phospholipase A2 Activitymentioning
confidence: 99%
“…As the Pla2 activity is significantly reduced in brain tissues [38,60] as well cerebrospinal fluid of patients with AD when compared to controls [42], we investigated whether LiCl would modulate Pla2 mRNA levels and/or enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentration was determined with the Bio-Rad DC Protein Assay (Bio-Rad, Hercules, CA, USA), modified from Lowry et al [55]. Briefly, the substrate used was L-α-1-palmitoyl-2-arachidonyl-phosphatidyl-choline labeled with [l- 14 C] in the arachidonyl tail at position sn-2 ( 14 C-PC) (48 mCi/ mmol specific activity, PerkinElmer, Boston, MA) [56][57][58][59][60], with slight modifications. Prior to the enzymatic reaction, a mixture of arachidonyl-l-14 C-PC and toluol-ethanolbutylhydroxytoluol antioxidants (1:10, v/v) was evaporated under a nitrogen stream (0.075 μCi per sample), resuspended in a solution of 0.3 mg/mL BSA in ultrapure water and homogenized by sonication.…”
Section: Radioenzymatic Analysis Of Pla2 Activitymentioning
confidence: 99%